The V's pillars of success - Padma, K.; Glenn, Rosemarie O; Senathirajah, Sathie; Singh, Bikramjit; Balagtas, Chandravali dasi; VStudios ([S.l.] : V-Studios, 2008)
The V partners talk on 4 V's pillar of success. This 4 series of program discuss the most important thing that people should do to success in this multilevel marketing
Title from container
Executive producer, Pathman Senathirajah ; editor, Ranjan Manikam
Speaker: K. Padma (part 1), Rosemarie O Glenn (part 2), Sathi Senathirajah (part 3), Bikramjit Singh (part 4)
DVD format
Keywords: Multilevel marketing; Direct marketing